(untitled) (Journal of Social Sciences Review, 2023)
This study examines the Kulturkampf, a major 19th-century German event in which Otto von Bismarck fought to limit Catholic influence in politics. Catholicism remained a powerful influence in German society despite Bismarck’s efforts, posing a difficult challenge to the mid-1800s political scene. Start with the Kulturkampf, the Catholic Church’s fight to adapt to liberal ideals, democracy, nationalism, socialism, and the industrial revolution. Liberal Catholicism’s answer to modernity is analyzed, focusing on Ignaz von Dollinger, who strove to reconcile faith with intellectual currents. The paper discusses the First Vatican Council in 1870, which introduced papal infallibility, and liberal Catholicism’s downfall. Germany is highlighted because Catholicism suffered ideological struggles and gained academic support as a secular, Protestant-influenced religion. Bismarck’s Catholicism onslaught from 1853-54 to the Kulturkampf of the 1870s is examined. Bismarck’s fears of Catholic violence and a Catholic plot are examined in the study. The issue deepened in 1873 when the May Laws sought state control over the Catholic Church. The Prussian bishops’ resistance to the May Laws led to incarceration, penalties, and institution closures. Bismarck’s authoritarianism failed to suppress Catholicism despite overwhelming opposition. Conclusions highlight the Kulturkampf legislation’ impact on church-state relations and the reduction of anti-Catholic measures. This paper analyzes historical events to reveal Bismarck’s political maneuvers, the Catholic Church’s struggles, and the Kulturkampf’s lasting effects on 19th-century Germany’s religious and political landscape.